FORMULASI SEDIAAN LOTION EKSTRAK ETANOL BIJI KOPI ROBUSTA (Coffea cenephora) - Wati, Erda; cahya, uci dwi; Darmirani, Yosi (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Bean robusta coffee contains polyphenol compounds which are useful as antioxidants. Antioxidants can inactivate the development of oxidation reactions, by preventing the formation of free radicals. Robusta coffee bean plant (Coffea canephora) is an ingredient that can be formulated into lotion preparations. Cosmetic lotion aims to remove dead skin cells, brighten the skin and soften the skin. This research is to make lotion preparations from robusta coffee bean extract (Coffea Canephora) . This research uses pure experiment. Robusta coffee beans are extracted by maceration process. The lotion formulation is made with variations of robusta coffee bean powder (Coffea Canephora) with a concentration of 2%, 3%, and 4%. The characteristic test includes organoleptic test, homogeneity test, Ph test, and irritation test. The purpose of this study was to determine the lotion formulation for robusta coffee bean extract (Coffea Canephora). The results of the lotion test had a homogeneous concentration of 2%, 3% and 4%, light brown to blackish brown, with a distinctive smell of coffee. The ph lotion test had a PH of 5 in all formulations on the blank had a PH of 6. The irritation test on the lotion preparation showed no erythema and edema in 5 volunteers. From all the tests carried out, the lotion formulation has good characteristics.